Does Maternal Stress Affect the Early Embryonic Microenvironment? Impact of Long-Term Cortisol Stimulation on the Oviduct Epithelium - Du, Shuaizhi (Int J Mol Sci, 2020)
Maternal stress before or during the sensitive preimplantation phase is associated with reproduction failure. Upon real or perceived threat, glucocorticoids (classic stress hormones) as cortisol are synthesized. The earliest “microenvironment” of the embryo consists of the oviduct epithelium and the oviductal fluid generated via the epithelial barrier. However, to date, the direct effects of cortisol on the oviduct are largely unknown. In the present study, we used a compartmentalized in vitro system to test the hypothesis that a prolonged stimulation with cortisol modifies the physiology of the oviduct epithelium. Porcine oviduct epithelial cells were differentiated at the air–liquid interface and basolaterally stimulated with physiological levels of cortisol representing moderate and severe stress for 21 days. Epithelium structure, transepithelial bioelectric properties, and gene expression were assessed. Furthermore, the distribution and metabolism of cortisol was examined. The polarized oviduct epithelium converted basolateral cortisol to cortisone and thereby reduced the amount of bioactive cortisol reaching the apical compartment. However, extended cortisol stimulation affected its barrier function and the expression of genes involved in hormone signaling and immune response. We conclude that continuing maternal stress with long-term elevated cortisol levels may alter the early embryonic environment by modification of basic oviductal functions.